Enhancing Website Management Through Expertise and Rapid Application Development Frameworks - Widodo, Eko; Setiawan, Ruben William; Dasra, Muhamad Nur Agus; Singgalen, Yerik Afrianto (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
Effective website management is crucial for organizations seeking to engage users and communicate effectively with stakeholders. This research explores the role of specialized expertise in typography, audio and visual design, copywriting, and the implementation of Rapid Application Development (RAD) frameworks in optimizing website management practices. By leveraging the skills of typography, design, and copywriting specialists, organizations create visually appealing and engaging online experiences that effectively convey messages and drive user interaction. Additionally, adopting RAD methodologies enables agile and iterative website development processes, allowing for quick prototyping, feedback integration, and rapid deployment of updates. Through synthesizing expert knowledge and RAD principles, organizations enhance their online presence, meet the evolving needs of users and stakeholders, and achieve their strategic objectives in today's dynamic digital landscape.